2023
DOI: 10.1002/slct.202302906
|View full text |Cite
|
Sign up to set email alerts
|

Interface‐Guided Computational Protein Design Reveals Bebtelovimab‐Resistance Mutations in SARS‐CoV‐2 RBD: Correlation with Global Viral Genomes and Bebtelovimab‐Escape Mutations

Shweata Maurya,
Shivank Kumar,
Aditya K. Padhi

Abstract: The emergence of novel mutations in the SARS‐CoV‐2 spike protein challenges monoclonal antibody (mAb) effectiveness. Comprehending resistance mutations and pinpointing vulnerable spike protein residues is vital for enhanced antibody design. To address this issue, we employed an interface‐guided computational protein design (CPD) approach to decode bebtelovimab‐resistance mutations and uncover susceptible residues within the receptor‐binding domain (RBD). Utilizing structural‐modeling and high‐throughput techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In some of our previous studies, we implemented high-throughput protein design methodologies to figure out critical residues and mutations within the intracellular proteins of SARS-CoV-2, including RdRp, 33 main protease (M pro ), 32 and spike protein RBD, 26 impacting the adaptability of the virus to antiviral drugs and antibody therapeutics. This study delved into the design and analysis of nsp7 mutations that may have an impact on the stability, adaptation, and fitness of nsp7 dimers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some of our previous studies, we implemented high-throughput protein design methodologies to figure out critical residues and mutations within the intracellular proteins of SARS-CoV-2, including RdRp, 33 main protease (M pro ), 32 and spike protein RBD, 26 impacting the adaptability of the virus to antiviral drugs and antibody therapeutics. This study delved into the design and analysis of nsp7 mutations that may have an impact on the stability, adaptation, and fitness of nsp7 dimers.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent studies, we harnessed the power of high-throughput protein design methodologies to pinpoint critical residues and mutations within intracellular proteins including main protease (M pro ), RdRp, and spike protein receptor binding domain (RBD) of SARS-CoV-2, which could make the virus more tolerant and adaptable to antiviral drugs such as remdesivir, molnupiravir, favipiravir, nirmatrelvir and bebtelovimab. 21–26 While conducting this research, we found that mutational and residue-specific changes can induce relative stabilities and adaptability of the RdRp, for instance, the nsp7 by forming symmetrical dimers. 20 This realization prompted us to perform an extensive protein design and ML-based endeavour, which was further complemented by a comprehensive multi-parametric analysis.…”
Section: Introductionmentioning
confidence: 93%